Epyllia and Epithalamia: Some Narrative Frames for Early Opera. (1st September 2020) - Carter, Tim
ABSTRACT: The first operas were often associated with princely wedding festivities, such as Jacopo Peri's Euridice (Florence, 1600) or Claudio Monteverdi's Arianna (Mantua, 1608). They formed part of a series of indoor and outdoor entertainments which, in turn, might plausibly be compared with the fresco cycles often commissioned to mark such nuptials. This also prompts reading them as epyllia, i.e. stories within the 'story' presented by their festivities as a whole. The concept is useful because their literary sources are usually themselves epyllia in an epithalamic context, as with Catullus's Poem 64 on the wedding of Peleus and Thetis. Representing such embedded narratives further encouraged multiple allegories through intertextual association. Situating early opera in the context of the broader tropes of princely celebration further helped overcome one absurdity of the genre: the fact that people sing.